2016
DOI: 10.1186/s40249-016-0111-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of meteorological factors on malaria patients in demilitarized zones in Republic of Korea

Abstract: BackgroundThe trend of military patients becoming infected with vivax malaria reemerged in the Republic of Korea (ROK) in 1993. The common explanation has been that infective Anopheles mosquitoes from the Democratic People’s Republic of Korea have invaded Republic of Korea’s demilitarized zone (DMZ). The aim of this study was to verify the relationship between meteorological factors and the number of malaria patients in the military in this region.MethodsThe authors estimated the effects of meteorological fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…As shown in Figure 4, the primary cluster of malaria was detected in the GADM level 3 administrative area of Paju-si (p < 0.001), and the secondary cluster was identified in the GADM level 3 administrative areas of Gimpo-si and Goyang-si (p < 0.001). We found that AEGIS was able to describe geographic distribution and identify the known primary cluster of malaria in case of Paju-si [35][36][37]. The main reason for this phenomenon is consistent with the opinion that the infective mosquitoes of North Korea flowed into South Korea through the western part of the military demarcation line [39,40].…”
Section: Identification Of Endemic Areas Of Malariasupporting
confidence: 83%
See 1 more Smart Citation
“…As shown in Figure 4, the primary cluster of malaria was detected in the GADM level 3 administrative area of Paju-si (p < 0.001), and the secondary cluster was identified in the GADM level 3 administrative areas of Gimpo-si and Goyang-si (p < 0.001). We found that AEGIS was able to describe geographic distribution and identify the known primary cluster of malaria in case of Paju-si [35][36][37]. The main reason for this phenomenon is consistent with the opinion that the infective mosquitoes of North Korea flowed into South Korea through the western part of the military demarcation line [39,40].…”
Section: Identification Of Endemic Areas Of Malariasupporting
confidence: 83%
“…The Korea Central Cancer Registry is a database that collects nationwide hospital-based cancer incidence data since 1980 and annually provides incidence, survival, and prevalence statistics [34]. To assess the credibility of the clustering findings generated from AEGIS, the geographical cluster of malaria in South Korea was compared with that of the previously published studies [35][36][37].…”
Section: Verification Of Methodological Quality Of Aegismentioning
confidence: 99%
“…In terms of the types of health outcomes other than death or cardio-cerebrovascular disease, the most frequently published (n=30) health outcome was infectious disease ( Figure 3). To be more specific, among studies focusing on vectorborne diseases, the association between ambient temperature and malaria was the most frequently studied [50][51][52][53][54][55][56][57][58][59][60]. Each study had a different range of lag effects.…”
Section: Domain 2: Effect Of Ambient Temperature On Other Health Outcmentioning
confidence: 99%
“…This puts US troops at risk of exposure if military forces press north. Furthermore, malaria was eradicated in South Korea in the 1970s, but soldiers (and increasingly, civilians as well) have been diagnosed with P. vivax malaria in the North-South demilitarized zone (Lee et al., 2002; Im et al., 2018), including reports of natural hybridization between local mosquito species and changing meteorological factors, to further perpetuate current observation (Choochote et al., 2014; Phasomkusolsil et al., 2014; Chang et al., 2016; Hwang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%